A Cross-Cultural Investigation of the Association between Betrayal Trauma and Dissociative Features. Issue 1 (January 2023) - Fung, Hong Wang; Chien, Wai Tong; Chan, Chitat; Ross, Colin A.
Betrayal trauma theory proposes that betrayal and non-betrayal traumas are different in terms of their nature and impacts. The theory predicts that dissociation is more strongly related to betrayal than to non-betrayal trauma, however there is a lack of cross-cultural evaluation of the theory. One competing theory is the socio-cognitive model, which proposes that dissociative amnesia (DA) and identity dissociation (ID) are the results of social influence and are not trauma-related conditions. This study aimed to test the hypotheses based on betrayal trauma theory and investigated the relationship between trauma, dissociation and other mental health problems in two culturally different convenience samples of people seeking web-based educational interventions for dissociation ( N = 83 English speakers and N = 82 Chinese speakers). Compared with childhood non-betrayal trauma, childhood betrayal trauma had a statistically stronger relationship with dissociation and borderline personality disorder (BPD) symptoms in both samples. DA and ID symptoms were cross-culturally associated with childhood betrayal trauma after controlling for other variables (including sample membership, age, depression levels, medication treatment and non-betrayal trauma). Participants with DA/ID symptoms reported significantly more trauma-related symptoms in both samples. The findings supported the cross-cultural application of the betrayal trauma theory for dissociative features and BPD symptoms. Implications for research and practice (e.g., child protection, assessment for survivors of childhood betrayal trauma) are highlighted.